Gender differences in reading comprehension via multimedia visual presentations / Syarifah Nurulaini Syed Abdul Mutalib - Syed Abdul Mutalib, Syarifah Nurulaini (2009)
The similarities and differences in how male and female students learn are important as these facts provide valuable information for more successful planning such as selecting suitable media and learning strategies that would benefit both genders. Although one way to improve the achievement of low-achieving students in the classrooms is by using different kinds of instructional strategies (Brannon, 2002), numerous researches had supported the evidence that using visuals in teaching could enhance learning (Rakes & Rakes, Smith, 1995; Beeland, 2001; Hudgins, 2005; Chambers, B., et al., 2005). The purpose of this action research study is to see whether gender differences in reading comprehension via multimedia visual presentations exist and to examine the effects of their learning styles on reading comprehension. This experimental study investigates how effective this technique can enhance low-achieving students reading comprehension regardless their learning styles and genders. This action research utilized quantitative and qualitative approach as each approach might reveal important findings that another approach fails to capture. A total of 35 lower secondary students (form one) from a school located in Bandar Country Homes, Rawang had participated in this study. These students were taught to read short story by using Microsoft power point presentation which contains text accompanied by a lot of pictures. Data from the students’ scores in their pre-test and post-tests were collected to examine the effectiveness of this approach and to compare whether there are any significant differences in gender in reading comprehension via multimedia visual presentations. The findings of the study indicated a strong preference for the use of multimedia visual presentations for both genders based on students' engagement and performances in the test given although female students showed better achievement in their reading comprehension using visuals. The result of this study is hoped to give suggestions for the teachers in planning their lesson wisely as they should consider selecting strategies that have great potential for improving and raising the academic achievement of both genders and thus, contribute and provide more knowledge in a growing body of research.